Phosphoenolpyruvate carboxylase, NADP-malic enzyme, and pyruvate, phosphate dikinase are involved in the acclimation of Nicotiana tabacum L. to drought stress - Doubnerová Hýsková, Veronika; Miedzińska, Lucia; Dobrá, Jana; Vankova, Radomira; Ryšlavá, Helena (Journal of plant physiology, 2014)
Drought stress is one of the most frequent forms of abiotic stresses, which occurs under condition of limited water availability. In this work, the possible participation of phosphoenolpyruvate carboxylase (EC 4.1.1.31; PEPC), NADP-malic enzyme (EC 1.1.1.40; NADP-ME), and pyruvate, phosphate dikinase (EC 2.7.9.1; PPDK) in response to drought of tobacco plants (Nicotiana tabacum L., cv. W38) was investigated. Enzyme specific activities in tobacco leaves of drought stressed plants were significantly increased after 11 days of stress, PEPC 2.3-fold, NADP-ME 3.9-fold, and PPDK 2.7-fold compared to control plants. The regulation of PEPC and NADP-ME activities were studied on transcriptional level by the quantitative RT PCR and on translational level - immunochemically. The amount of NADP-ME protein and transcription of mRNA for chloroplastic NADP-ME isoform were increased indicating their enhanced synthesis de novo. On the other hand, mRNA for cytosolic isoform of NADP-ME was decreased. The changes in PEPC protein and PEPC mRNA were not substantial. Therefore regulation of PEPC activity by phosphorylation was evaluated and found to be involved in the stress response. During recovery, activities of the tested enzymes returned close to their basal levels.
Keywords: Stress, Physiological; Acclimatization; Pyruvate, Orthophosphate Dikinase; Droughts; listy rostlin; období sucha; Plant Proteins; Nicotiana; Chloroplasts; aklimatizace; Plant Leaves; Nicotiana tabacum L.; Drought; pyruvátfosfátdikinasa; Pyruvate, phosphate dikinase; rostlinné proteiny; fyziologický stres; fosfoenolpyruvátkarboxylasa; chloroplasty; Phosphoenolpyruvate carboxylase; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; Malate Dehydrogenase; NADP-malic enzyme; Phosphoenolpyruvate Carboxylase; malátdehydrogenasa; tabák; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction